2014
DOI: 10.7903/cmr.11666
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Activities of Female Foreign Workers in Taiwan: Transnationalism, Feminism and Work Arrangements

Abstract: The number of foreign workers in Taiwan is increasing. As a result, such workers' leisure activities outside of the workplace have become a strong area for research on work and leisure. In terms of transnationalism, feminism, and work arrangements, this study proposes to examine the leisure activities of female foreign workers. The aim of the study has three aspects: first, to examine to what extent transnationalism and feminism operate to influence the leisure activities of female foreign workers, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For example, Hsu and Hsu [84] observed that although Indonesian care workers in Taiwan had limited discretionary time, they still participated in various leisure activities, such as travel. Tsai [85] focused on female blue-collar foreign workers and examined their leisure activities after work in Taiwan, observing that their leisure activities were affected by their countries or origin and their work arrangements. Furthermore, Tsai [86] also discussed foreign white-collar workers' leisure opportunities in Taiwan and showed that most respondents regularly participated in leisure or sports activities after work.…”
Section: Tourism Behavior For Foreign Workers and A Given Groupmentioning
confidence: 99%
“…For example, Hsu and Hsu [84] observed that although Indonesian care workers in Taiwan had limited discretionary time, they still participated in various leisure activities, such as travel. Tsai [85] focused on female blue-collar foreign workers and examined their leisure activities after work in Taiwan, observing that their leisure activities were affected by their countries or origin and their work arrangements. Furthermore, Tsai [86] also discussed foreign white-collar workers' leisure opportunities in Taiwan and showed that most respondents regularly participated in leisure or sports activities after work.…”
Section: Tourism Behavior For Foreign Workers and A Given Groupmentioning
confidence: 99%
“…In the use of public space, the public has given a more lenient standard to men. Mainstream values of Taiwanese society deem that it is not easy for women to be influential in the group, unless they perform better in the group, provide more positive suggestions, and do not blindly succumb to men in the organization (Tsai, 2014 With patriarchal influence, not to mention the vast majority of resources and development being focussed on men, women's leisure is thus oppressed. Double standards give women greater pressure, leading to their reluctance to leave home to go to public areas for leisure activities (Tsai, 2010b).…”
Section: Findings and Discussionmentioning
confidence: 99%